Screening, identification and immobilization of ammonia oxidizing bacterial consortium collected from mangrove areas and shrimp farms - Natnan, Maya Erna; Banerjee, Sanjoy; Mohamed Din, Mohamed Shariff; Md. Yusoff, Fatimah (Academic Journals, 2013)
The immobilization of nitrifying bacteria in alginate has been used to evaluate the performance of ammonia reduction. In this research, bacteria were screened and observed for their ability to reduce ammonia. Consortium M1, isolated from the mangrove area (Morib, Selangor) showed the most effective reduction of ammonia from an initial concentration of 2.17±0.10 to 0.06±0.01 mg L-1 in 14 days. The consortium was then identified to consist of Pseudomonas aeruginosa (99%), Pseudomonas stutzeri (98%) and Nocardioides albus (98%) using the 16S rDNA gene sequences via Polymerase Chain Reaction (PCR) technique and identified by phylogenetic analysis based on their partial 16S rDNA sequences comparison in NCBI GenBank. The consortium M1 was then immobilized into alginate beads each containing 1.79x103 CFU mL-1 bacteria cells before being tested for its efficacy in reducing ammonia under laboratory conditions using 10, 20, 30, 40, 50, 100, 150 and 200 beads. The fastest reduction rate of Total Ammonia Nitrogen (TAN) was observed in flasks containing 150 beads which on day 6, drastically reduced TAN from 2.50±0.10 to 0.090±0.059 mg L-1 followed by treatment with 200 beads (0.104±0.07 mg L-1). However, at the end of experiment at day 14, the lowest TAN level (0.083±0.063 mg L-1) was observed in flasks with 200 beads which was not significantly different (p>0.05) from flasks with 150 beads (0.106±0.034 mg L-1). The present study reveals that the immobilization of bacterial consortium consisting of ammonia oxidizing bacteria could be used as an alternative for reduction of high TAN concentration in shrimp or fish hatchery system.